2003
DOI: 10.2174/1381612033455305
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Design Approaches to Cell Wall Biosynthesis Inhibitors

Abstract: This review summarizes some of the published attempts to incorporate protein and NMR structures in the design of new antibiotics that specifically target Cell Wall biosynthesis. Most of the steps involved in peptidglycan synthesis have been investigated as potential strategies against cell wall inhibition. Structural information has been most useful in the design of molecules in the Mur enzyme pathway, penicillin binding proteins and lactamases, as well as proteins that are part of the final steps of transglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 0 publications
0
32
0
1
Order By: Relevance
“…Isomorphous cocrystals of the LL-AziDAP-and DLAziDAP-inhibited forms of DAP epimerase belong to space group C222 1 . Both structures were solved by molecular replacement and refined to respectable R factors.…”
Section: Resultsmentioning
confidence: 99%
“…Isomorphous cocrystals of the LL-AziDAP-and DLAziDAP-inhibited forms of DAP epimerase belong to space group C222 1 . Both structures were solved by molecular replacement and refined to respectable R factors.…”
Section: Resultsmentioning
confidence: 99%
“…The subsequent steps in the pathway are entirely dependent on the MurB product UDP-MurNAc for completion and delivery of peptidoglycan monomer units to actively growing regions of the bacterial cell wall. Due to its importance in peptidoglycan biosynthesis, the MurB enzyme has been the subject of a number of target-based drug design efforts (8,18,21,36,39,69).…”
mentioning
confidence: 99%
“…The absence of a homologue in eukaryotic cells makes MurB an attractive target for small molecule inhibitors with the potential to have broad antibacterial activity. Biochemical characterization and X-ray structural analysis of MurB from Escherichia coli (3-5, 18, 45), S. aureus (6), and Streptococcus pneumoniae (49) have been published and have been used in structure-based approaches to design inhibitors (30). Based on a cocrystal structure study of E. coli MurB with enolpyruvyl-UDP-N-acetylglucosamine (EP-UNAG) (3,4), it was found that the carboxylate of the substrate interacts with residues Arg159 and Glu325 and may be responsible for transition state stabilization, whereas the diphosphate moiety of the substrate interacts with residues Tyr190, Lys217, Asn233, and Glu288.…”
mentioning
confidence: 99%